Drug-Induced Liver Injury in Paediatrics: A Short Review - Tei, Monica; Lotti, Federica; Storelli, Flavio; Grosso, Salvatore (International Journal of Pediatrics and Child Health, 2022)
Drug-induced liver injury (DILI) is an under-recognized cause of paediatric liver disease. Although DILI in children accounts for about 1% of all reported adverse drug reactions throughout all age groups and less than 10% of all clinical DILI cases, it is responsible for about 20% of acute liver failure (ALF) cases. A wide range of drugs, herbal products and nutritional supplements have been associated with the development of DILI through dose-dependent, idiosyncratic or indirect mechanism. Limited literature is available in pediatric population, making DILI a still challenging diagnosis. An accurate medical history is of pivotal importance and should investigate about drug consumption, clinical and laboratory findings, individual and family risk factors for drug-related side effects or comorbidities, the timing of the injury onset after the implicated agent has been started (latency). Clinical presentation of DILI varies from asymptomatic or very mild to serious and sometimes fatal conditions; laboratory tests may be helpful in ruling out other causes of liver injury but, with few exceptions, they are aspecific. Early suspicion and prompt withdrawal of the offending drug play a key role for a successful management of most cases. Rarely a specific therapy is available, as for acetaminophen toxicity, treated with N-acetylcysteine, and sodium valproate toxicity, where carnitine may be beneficial. Although controlled trials are not available yet, corticosteroids and ursodeoxycholic acid can be considered if no improvement is proven after discontinuation of drug. The present short review is not intended to deal with all aspects concerning DILI but to focus on epidemiology, pathogenesis, clinical features, practical management and current challenges in paediatric age.